Pengaruh Kemiskinan terhadap Praktik Dinasti Politik di Indonesia dan Filipina Tahun 2017-2021 - Pradikta, Hikam Putra (Global Focus, 2024)
This article aims to determine the influence between poverty and the expansion of political dynasties in the Philippines and Indonesia in 2017-2021. To provide comprehensive empirical, testing is carried out using multiple linear regression tests. The author uses multiple linear regression tests. The author uses three independent variables representing wealth through the variable Gross Domestic Product (GDP) Per Capita, welfare through the Human Development Index (HDI), and inequality through the Gini Ratio. As a result, the author finds empirical findings about the influence of poverty on political dynasties in both countries. In the Philippines, only wealth and prosperity can affect political dynasties. While in Indonesia, only wealth and prosperity can affect political dynasties. In general, poverty in both countries contributes to the expansion of political dynasties. Keywords: poverty, political dynasty, multiple linear regression